Nitrate–nitrite equilibrium in the reaction of NO with a Cu-CHA catalyst for NH3-SCR. Issue 23 (3rd November 2016) - Tyrsted, C.; Borfecchia, E.; Berlier, G.; Lomachenko, K. A.; Lamberti, C.; Bordiga, S.; Vennestrøm, P. N. R.; Janssens, T. V. W.; Falsig, H.; Beato, P.; Puig-Molina, A.
Abstract : A multi-technique in situ study of the reaction between NO and Cu-nitrates in the Cu-CHA deNO x catalyst yields novel structural and spectroscopic insights into the equilibrium between Cu-nitrates and Cu-nitrites, which was proposed as key step in the NH3 -SCR cycle. Abstract : The equilibrium reaction between NO and Cu-nitrate, Cu(ii )-NO3 − + NO(g) ⇌ Cu(ii )-NO2 − + NO2 (g), has been proposed to be a key step in the selective catalytic reduction of NO by ammonia (NH3 -SCR) over Cu-CHA catalysts and points to the presence of Cu-nitrites. Whereas the formation of gaseous NO2 has been observed, a direct observation of Cu-nitrite groups under conditions relevant to NH3 -SCR has been so far unsuccessful. In an effort to identify and characterize Cu-nitrites, the reaction between Cu-nitrates hosted in the CHA zeolite and NO is investigated by Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-vis) and X-ray absorption spectroscopy (XAS). We find that NO reacts with Cu-nitrates and that about half of the Cu-nitrate species are converted. After the reaction, the Cu(ii ) state is different from the original oxidized state. Analysis of XAS data indicates that the final state of the Cu-CHA catalyst is consistent with the partial conversion of the Cu-nitrate species to a bidentate Cu-nitrite configuration.